Effect of Scientific Approach toward Students' Critical Thinking Skills - Triyani Triyani; Lovy Herayanti; Syifaul Gummah (Universitas Pendidikan Mandalika, 2019)
The role of education is to improve the quality of education, especially in producing high-quality students. High-quality students are those who are able to think critically, creatively, logically and take initiatives in responding to issues in society caused by the impact of the development of science and technology. This study aims to determine the effect of a scientific approach to students' critical thinking skills. This study is an experimental research with one group pretest-posttest design. The sample of this study consisted of one class (28 students), which was treated using a scientific approach. Critical thinking skills are measured using a test instrument and then analyzed statistically (t test). Hypothesis test results indicate that there is an effect of using a scientific approach toward students' critical thinking skills.